BIOMASSA E FLORA EPIFÍTICA DE COPAS DE Araucaria angustifolia - Ruiz, Emilio Carlos Zilli (2017)
The objective of this research was to evaluate and model the aerial biomass of Araucaria angustifolia (Bertol) Kuntze in fragments of Mixed Ombrophilous Forest, as well as to analyze the richness, diversity and distribution of vascular epiphytes in forophytes of this species. It was used primary data from 30 native trees managed in a Research and Extension Project of the Department of Forestry of UNICENTRO. The research methodology was descriptive, analytical with primary data, in a quantitative approach. For trunk with bark biomass samples were taken from the tree to determine the mean basic density and then extrapolated to the entire tree by means of the trough. In relation to the leaf twigs and branches, the base circumference and length of 209 branches and weights were measured to fit equations. The circumference of the knot of the broken branches was also measured to estimate the dry mass of these branches. For the epiphytes, trees were divided into three vertical sampling zones and all individuals were identified and recorded in their respective zones. The average length of the branches was 4.06 m and the base circumference was 24.04 cm, that is, 7.65 cm diameter. The average dry masses of leaf twigs and branches were 6,473 and 1,644 kg, respectively. For the estimates of the dry masses of leaf twigs and branches, when inserted in the model variables related to length and circumference, the adjustments had the best results, followed only by the circumference, with close results, and the length. For all cases, it was necessary to transform the dependent variable to meet the normality of residues and homogeneity in the variances. Regarding partial and total aerial biomass, 77.00 % of the dry mass came from the trunk with bark, 18.26 % from the branches and 4.74 % from the leaf twigs. For the estimates of total aerial dry mass, trunk with bark and branches, DHB showed a higher correlation with Pearson's correlation (r) of 0.93, 0.95 and 0.79, respectively. For the dry mass of leaf twigs, the highest correlation was with crown length (r = 0.76). As for dry mass of leaf twigs, branches and trunk with bark, as well as aerial total, the Spurr model presented the best R²adj and Syx results, but the β0 coefficients of all the equations were not significant at 1%. Thus, for dry mass of leaf twigs, the most suitable model was the single entry linear with crown length (R²adj = 0.515 and Syx = 24.48%); For the branches, the simple entry with the DHB in absolute value (R²adj = 0.604 and Syx = 35.30%); Schumacher-Hall was the most suitable model for the trunk with bark (R²adj = 0.936 and Syx = 8.92%). This model was also the most adequate for the total (R²adj = 0.885 and Syx = 12.82%). Also, 2,837 individuals of vascular epiphytes belonging to 25 species were collected. The Orchidaceae family showed higher species richness (11) followed by Polypodiaceae (seven). For abundance, these families also presented more individuals being Polypodiaceae with 54,38% of the total and Orchidaceae, 13,57%. The crown showed a greater species richness (21), followed by the base and the stem, and greater abundance with 69.16% of the total raised. Ten species occurred only in the canopy, three at the base and six at the three sampling sites. Microgramma squamulosa and Pleopeltis hirsutissima were the most representative species, and the Shannon Index was 0.202 and Pielou 0.684. Therefore, as main conclusions can be affirmed that the native Araucaria branches present large dimensions that can be used in specific uses, besides these trees have high biomass and the DHB is very correlated with this variable. The epiphytic flora in Araucaria was very rich and diverse, with the crown being the main environment of this group of plants.